PENGARUH TOTAL QUALITY CONTROL DAN JUST IN TIME TERHADAP PENINGKATAN KUALITAS PRODUK DAN EFISIENSI BIAYA - Hasanah, Robiatul; R. Pandin, Maria Yovita (Universitas 17 Agustus 1945 Surabaya, 2021)
The research entitled Effect of Total Quality Control and Just In Time on improving product quality and cost efficiency aims to analyze the effect of Total Quality Control (TQC) and Just In Time (JIT) on improving product quality and cost efficiency. This research was conducted at one of the manufacturing companies in Surabaya, namely UD. Sukri Dana Abadi. This study used descriptive qualitative method. The type of data used in this study is the type of primary data where researchers obtain data through direct data collection efforts. Methods of data collection is done by conducting interviews and observations on the object under study. The results of this study indicate that Total Quality Control (TQC) has an effect on improving product quality and cost efficiency, where the quality of the resulting product is in accordance with the specifications and Standard Operational Prosedur (SOP). While Just In Time (JIT) shows a significant effect on improving product quality and cost efficiency. The storage fee before Just In Time is Rp. 7,463,577 while the storage cost after Just In Time is Rp. 3,732,788 then there is a difference of Rp. 3,731,788 which means Just In Time can reduce costs by Rp. 3,731,788.